Assessing the turbulent kinetic energy budget in an energetic tidal flow from measurements of coupled ADCPs. (21st August 2020) - Thiébaut, Maxime; Filipot, Jean-François; Maisondieu, Christophe; Damblans, Guillaume; Duarte, Rui; Droniou, Eloi; Guillou, Sylvain
Abstract : Two coupled four-beam acoustic Doppler current profilers were used to provide simultaneous and independent measurements of the turbulent kinetic energy (TKE) dissipation rate ε and the TKE production rate P over a 36 h long period at a highly energetic tidal energy site in the Alderney Race. The eight-beam arrangement enabled the evaluation of the six components of the Reynolds stress tensor which allows for an improved estimation of the TKE production rate. Depth-time series of ε, P and the Reynolds stresses are provided. The comparison between ε and P was performed by calculating individual ratios of ε corresponding to P . The depth-averaged ratio ε / P averaged over whole flood and ebb tide were found to be 2.2 and 2.8 respectively, indicating that TKE dissipation exceeds TKE production. It is shown that the term of diffusive transport of TKE is significant. As a result, non-local transport is important to the TKE budget and the common assumption of a local balance, i.e. a balance between production and dissipation, is not valid at the measurement site. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.